Green intellectual capital driving green competitive advantage: The mediation of green innovation and transformational leadership - Pham, Ngoc Duong; Pham, Quoc Tri; Nguyen, Tuan; Ho, Vinh Hoa; Tham, Duc Hieu (Edelweiss Applied Science and Technology, 2025)
This article explores the complex relationships between Green Intellectual Capital (GIC), Green Innovation (GIN), Transformational Leadership (TFL), and Green Competitive Advantage (GCA), with a focus on the mediating roles of GIN and TFL in the connection between GIC and GCA. Using quantitative data collected from 315 directors and departmental managers in the manufacturing industry in Vietnam, the study applied a second-order PLS-SEM approach to analyze the relationships. The findings show that GIC positively influences GIN, TFL, and GCA, with GIN and TFL also exerting positive effects on GCA. Additionally, GIN and TFL serve as partial mediators in the relationship between GIC and GCA. This research contributes to sustainability management literature by offering new insights into the factors driving green competitive advantage. By integrating GIC, GIN, and TFL into a unified model, the study provides valuable strategic implications for firms seeking to develop sustainable competitive advantages through green innovation and leadership.